Pancytopenia: a clinico hematological study - Singh, Priti; Mohanty, Ramesh Chandra; Mohanty, Raghumani; Alam, Sadaf (International Journal of Research in Medical Sciences, 2016)
Background: Pancytopenia is very common consequence of many haematological diseases. It is the shortage of all types of blood cells. It happens in many serious and life-threatening illnesses, ranging from simple drug-induced bone marrow hypoplasia, megaloblastic anemia to fatal bone marrow aplasias and leukemias. It has different causes and severity based on which the treatment is directed and prognosis is implicated. Main objective of the study was to study the clinical presentations in pancytopenia due to various causes; and to evaluate hematological parameters, including bone marrow. Methods: It was a prospective study, and 50 pancytopenic patients were evaluated clinically, along with hematological parameters and bone marrow aspiration in Hematology Unit, Department of Pathology, Hi-Tech Medical College and Hospital, Bhubaneswar, Orissa, India during the period of October 2013 to September 2015. Results: Among 50 cases studied, age of patients ranged from 1 to 80 years with commonest age group being 41-50 years, and male predominance. Most of the patients presented with generalized weakness, pain abdomen and bleeding. Bone marrow aspiration was conclusive in all cases. The commonest marrow finding was hypocellularity followed by hypercellularity with megaloblastic erythropoiesis. The commonest cause for pancytopenia was aplastic anemia (44%), followed by mrgaloblastic anemia (20%). Conclusions: The present study concludes that detailed primary hematological investigations along with bone marrow aspiration in cytopenic patients are helpful for understanding disease process and to diagnose or to rule out the causes of cytopenia. These are also helpful in planning further investigations and management.